Effect of silver diamine fluoride solution application on the bond strength of dentine to adhesives and to glass ionomer cements: a systematic review - Meng Jiang; May Lei Mei; May Chun Mei Wong; Chun Hung Chu; Edward Chin Man Lo (BMC, 2020)
Abstract Background Silver diamine fluoride (SDF) solution gains increasing popularity in arresting dentine caries in clinical practice. The aim of this systematic review was to summarize the findings from laboratory studies on the influence of SDF application on the bond strength of dentine to various adhesives and to glass ionomer cements (GICs). Methods Two independent reviewers conducted a literature search in the databases Medline, Ovid, PubMed and Web of Science until 15th August 2019 using the search keywords ['bond strength'] AND ['silver diamine fluoride' OR 'silver diammine fluoride' OR 'SDF' OR 'silver fluoride' OR 'diamine silver fluoride']. Articles investigating the effect of SDF application on the bond strength of dentine to various adhesives and to GICs were included in this review. Information on how SDF application influenced the bond strength was extracted from the included articles. Besides, related information, e.g. test method of bond strength, concentration and brand of SDF, type of adhesive system and GIC, testing dental substrate, protocol of specimen preparation, and failure mode was also reviewed. Results A total of 13 articles were included in this review, with 8 and 6 studies investigating the effect of SDF application on the bond strength of dentine to various adhesives and to GICs, respectively. Sound dentine as well as demineralized dentine created by chemical methods, e.g. immersing in a demineralizing solution, was commonly adopted as the testing dental substrate. The microtensile bond strength (mTBS) test was the predominant method employed. However, the bond strength values had large variations among studies, ranging from <10 to 162 Mpa. Regarding the bond strength to different adhesives, 4 studies indicated that SDF application followed by rinsing with water had no significant influence. However, another 4 studies reported reduced bond strength after SDF application. Regarding the bond strength to GICs, 4 studies concluded that SDF application had no adverse impact on the bond strength. Conclusions No solid conclusion can be drawn on the effect of SDF application on the bond strength of dentine to adhesives and to GICs due to the high degree of variation of the included studies.